Altered Nuclear Expression of the Deubiquitylase BAP1 Cannot be Used as a Prognostic Marker for Canine Melanoma. (July 2018) - Jama, N.; Farquhar, N.; Butt, Z.; Coupland, S.E.; Sacco, J.J.; Scase, T.; Fielding, A.B.; Coulson, J.M.; Kalirai, H.; Killick, D.R.
Summary: BRCA1-associated protein-1 (BAP1) is a nuclear localized deubiquitylating enzyme that belongs to the ubiquitin c-terminal hydrolase subfamily. The encoded protein is highly homologous between man and dogs, suggesting a functional significance preserved by evolution. BAP1 has multiple properties, including tumour suppressor activity. Loss of BAP1 function is implicated in the oncogenesis of several types of cancers including uveal, mucosal and some cutaneous melanomas in humans, as well as in mesothelioma. In this study we investigate the significance of BAP1 in canine melanoma. Nuclear BAP1 protein was detected in five canine oral melanoma cell lines using an antibody commonly used for analysis of human tissues. BAP1 loss of function mutations often lead to loss of nuclear BAP1 (nBAP1) expression in humans; this is associated with a poorer prognosis in uveal and mucosal melanoma. Therefore, as a prelude to a study evaluating the prognostic significance of nBAP1 expression in dogs, immunohistochemistry (IHC) was used to assess cases of canine melanoma for nBAP1 expression. In 89 cases where tumour cells were identified by melan-A labelling, 100% of tumour cells were positive for nBAP1 expression, including eight uveal tract and 29 oral mucosal melanomas. This finding indicates that BAP1 IHC cannot be used as a prognostic marker in canine uveal and mucosal melanoma. Moreover, this observation suggests that either BAP1 has a different functional significance in canine melanoma or that loss of BAP1 function is achieved by a different route. This is a novel finding that warrants further investigation to determine the comparative biological relevance.